Aspectos microestruturais da liga Al64Cu28Fe8 depositada por laser cladding em substrato de aço AISI 304 - Farina, Maria Eduarda Tedesco (2021)
The Al64Cu28Fe8 alloy has an icosahedral quasicrystalline (IQC) phase that gives some typical characteristics of ceramic materials such as good resistance to corrosion and oxidation, low friction coefficient, high hardness and good wear resistance. These attributes contribute to the application of Al-Cu-Fe alloys in tool coatings, pipes and wear surfaces. The objective of this work was to study how the parameters of laser cladding influence the microstructural behavior of the Al64Cu28Fe8 alloy when deposited on a substrate of stainless steel AISI 304. Laser cladding is a melt coating process where a laser beam is used to melt metallic or ceramic powder onto a substrate. Parameters such as power, beam thickness, laser scanning speed, along with the composition and the amount of powder available during the process, determine the microstructure, thickness and depth of the deposit. The microstructure evaluation and deposit morphology were performed by scanning electron microscopy, microanalysis and X-ray diffraction. The results indicate that the laser cladding process is suitable for the deposition of the Al64Cu28Fe8 alloy on AISI 304 substrates. From the laser cladding process used in this experiment, the formation of deposits with a symmetric dilution zone and centralized in coatings with the IQC phase were obtained with linear input energy between 2.0 – 2.4 W.min/mm.